The Relationship between Loneliness and Perceived Quality of Life among Older Persons with Visual Impairments. (November 2015) - Grow, Steven J. La; Towers, Andy; Yeung, Polly; Alpass, Fiona; Stephens, Christine
Introduction: This article explores the rate and degree of loneliness in community-dwelling older visually impaired people, and is the first study to investigate the unique contribution that social and emotional loneliness makes to perceived quality of life (PQOL) in this population. Methods: The study constituted a secondary analysis of postal survey data from the second wave (2012) of the nationally representative New Zealand Longitudinal Study of Ageing, a longitudinal study of older New Zealanders. A total of 2, 683 participants completed both the visual status screening question and all 11 loneliness items to meet the criteria for inclusion in this study. Results: Those designated as being visually impaired ( n = 315) were found to be more likely to experience loneliness (53% vs. 36%) than their sighted peers ( n = 2, 368). Increased loneliness among those who are visually impaired was found to be associated with decreased economic well-being, mental health, satisfaction with activities of daily living, satisfaction with life, and PQOL. Social loneliness, but not emotional loneliness, was found to make a unique contribution to the prediction of variance in the PQOL of older visually impaired people over and above the impact of other predictors. Discussion: Loneliness is much more prevalent in, and occurs with greater severity among, people who are visually impaired than with those who are not. Social loneliness made a unique contribution to PQOL over and above the contribution of variables that previous research has shown are central to PQOL in this population. Implications for practitioners: Loneliness is not often addressed in vision rehabilitation programs designed for older adults, yet it is apparent from these findings that rates of loneliness may be high in this population. Its effect, even at moderate levels, is detrimental to the PQOL of older people with visual impairments.